The Relationship between Self-Efficacy and Readiness of Interprofessional Education (IPE) among Students at the Faculty of Medical and Health Sciences UIN Alauddin Makassar - Vovi Sulastri Akhmad; Saldi Yusuf; Ayu Safitri; Helmi Juwita; Risnah Risnah; Arbianingsih Arbianingsih (Journal of Health Science and Prevention, 2019)
Interprofessional education (IPE) needs to be introduced early in the academic stage to prepare health professionals who are expected to be more professional. Both self-efficacy and IPE readiness are vital considerations to achieve the goals regarding the implementation of IPE. The purpose of this study was to determine the relationship between self-efficacy and IPE readiness. This research used a descriptive correlation design with a cross-sectional approach. The sampling was 146 students and utilized 10% quota sampling from each major. This study consisted of two types of questionnaires, namely the self-efficacy questionnaire and Readiness of the Interprofessional Learning Scale (RIPLS). The collected data were analyzed using the Chi-Square test. The result of this study indicated that 56.8% of students have high self-efficacy. There are no students in low self-efficacy category. Then, the readiness of students on IPE is high, with 89.0%, and there are no students in low category. The Chi-Square test result shows that the value of p=0.006 or p<0.05. It means that there is a relationship between self-efficacy and readiness of IPE among students at FKIK UIN Alauddin Makassar. Therefore, to implement IPE, efforts need to be made to improve students’ self-efficacy and ultimately improve IPE readiness.